MODERN TRAINING METHODS FOR TEACHING TECHNICAL AND TACTICAL ACTIONS IN WRESTLING - Mamanazarov Akmal Anvarovich (International Journal of Literature and Language Studies, 2026)
This article provides a scientific analysis of modern training methods used in teaching technical and tactical actions in wrestling. It examines the interrelationship between technical and tactical preparation, the step-by-step process of their development, and their importance in competitive performance. The effectiveness of simulated training, situational training, video analysis, as well as interactive and differentiated approaches is substantiated. The article also highlights the importance of integrating technical-tactical preparation with physical and psychological training, as well as the use of modern technologies and monitoring tools. The results of the study demonstrate the necessity of a comprehensive and scientifically grounded approach to the effective development of technical and tactical skills.